Bimbingan dan konseling / Robert L. Gibson, Marianne H. Mitchell ; alih bahasa, Yudi Santoso. - GIBSON, Robert L.; Mitchell, Marianne H; Yudi Santoso (Pustaka Pelajar, 2011)
xxiv, 856 hlm. : ilus. ; 24 cm (3 eks.)